Forest Ecosystems in a Changing Environment : Identifying Future Monitoring and Research Needs 11-13 March 2008 Istanbul, Turkey - T.C. Orman Genel Müdürlüğü (COST, 2008)
Eser toplantı dokümanlarını da içermektedir.